2018
DOI: 10.1097/wco.0000000000000558
|View full text |Cite
|
Sign up to set email alerts
|

Episodic syndromes of childhood associated with migraine

Abstract: Episodic syndromes are considered to be early life expressions of migraine in the developing brain. Additional research is needed to determine, which acute and preventive treatments are the most effective in managing these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
1
9
0
1
Order By: Relevance
“…There is evidence in the literature supporting a brain‐gut connection 21 . This review further corroborates this association by providing evidence of shared pathophysiological features, such as alterations in serotonergic signaling 35–43 and autonomic dysfunction, 20,22–24,26–28,30,31 and overlapping symptomatology between migraine, 1,4,5,7,11,14,18,44–53 and GI disorders including gastroparesis, functional dyspepsia, and cyclic vomiting syndrome, often presenting as comorbidities in either condition 7,10,11,54–58 …”
Section: Pathophysiological Similarities Between Gi Comorbidities and Migrainesupporting
confidence: 69%
See 1 more Smart Citation
“…There is evidence in the literature supporting a brain‐gut connection 21 . This review further corroborates this association by providing evidence of shared pathophysiological features, such as alterations in serotonergic signaling 35–43 and autonomic dysfunction, 20,22–24,26–28,30,31 and overlapping symptomatology between migraine, 1,4,5,7,11,14,18,44–53 and GI disorders including gastroparesis, functional dyspepsia, and cyclic vomiting syndrome, often presenting as comorbidities in either condition 7,10,11,54–58 …”
Section: Pathophysiological Similarities Between Gi Comorbidities and Migrainesupporting
confidence: 69%
“…18,28 Migraine is also a frequent comorbidity present in individuals with CVS, including children. 56,57 In a retrospective study by Fleisher et…”
Section: Cvs and Migrainementioning
confidence: 99%
“…There are some indications that babies with colic become children at increased risk for recurrent abdominal pain or become adults who have more frequent FGIDs or mood disorders than a control healthy infant population without colic 7 . It has been suggested that infants with infantile colic are at increased risk of developing migraine 8 . However, well-designed long-term, prospective, observational studies are needed to endorse the few reports on possible associations between infantile colic and later health outcomes.…”
Section: What Is Infantile Colic?mentioning
confidence: 99%
“…Patients with migraine are likely to have a medical history of infant colic, and an infant with colic tends to have parents with migraine [12, 13]. And infant colic is considered to be early expression of migraine [14]. TTH and migraine exhibit similar pathogenic mechanisms, resulting from the dysfunction of nociceptive pain processing [15].…”
Section: Introductionmentioning
confidence: 99%